2018
DOI: 10.3389/fcimb.2018.00058
|View full text |Cite
|
Sign up to set email alerts
|

Hypoacylated LPS from Foodborne Pathogen Campylobacter jejuni Induces Moderate TLR4-Mediated Inflammatory Response in Murine Macrophages

Abstract: Toll-like receptor 4 (TLR4) initiates immune response against Gram-negative bacteria upon specific recognition of lipid A moiety of lipopolysaccharide (LPS), the major component of their cell wall. Some natural differences between LPS variants in their ability to interact with TLR4 may lead to either insufficient activation that may not prevent bacterial growth, or excessive activation which may lead to septic shock. In this study we evaluated the biological activity of LPS isolated from pathogenic strain of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
(61 reference statements)
1
7
0
1
Order By: Relevance
“…Considering that the breast lactation metabolism is correlated with breast cancer tumorigenesis ( Kim and Wysolmerski, 2016 ; Wani et al, 2017 ), this microorganism is regarded as a potential quantitative parameter for breast cancer. Many studies have identified the infection of Campylobacter in breast cancer ( Korneev et al, 2018 ; Parida and Sharma, 2019 ), further validating the efficacy and the accuracy of our prediction.…”
Section: Discussionsupporting
confidence: 62%
“…Considering that the breast lactation metabolism is correlated with breast cancer tumorigenesis ( Kim and Wysolmerski, 2016 ; Wani et al, 2017 ), this microorganism is regarded as a potential quantitative parameter for breast cancer. Many studies have identified the infection of Campylobacter in breast cancer ( Korneev et al, 2018 ; Parida and Sharma, 2019 ), further validating the efficacy and the accuracy of our prediction.…”
Section: Discussionsupporting
confidence: 62%
“…Сells were transfected with 1.8 μg of plasmid DNA and 0.2 μg of pRL-CMV Renilla luciferase control vector using X-treme Gene HP DNA Transfection Reagent (Roche, Basel, Switzerland) according to manufacturer’s protocol. Firefly luciferase activity was measured as described [ 71 ], and normalized to the activity of Renilla luciferase in order to account for the variations in cell transfection and lysis efficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…(Poxton and Edmond, 1995;d'Hennezel et al, 2017;Jacobson et al, 2018). Another example is the hypoacylated LPS from a foodborne pathogen Campylobacter jejuni that only moderately induces TLR4 dependent immune response (Korneev et al, 2018). Furthermore, Shigella flexneri 2a that contains a mixture of hexaacylated, pentaacylated, and predominantly tetraacylated lipid A in its LPS also significantly decreases its stimulatory effects on NF-kappaB signaling pathway in contrast to the hexaacylated E. coli LPS (Rallabhandi et al, 2008).…”
Section: Anti-inflammatory Lipopolysaccharides Is Characterized By Stmentioning
confidence: 99%